2020
DOI: 10.1055/a-1232-7292
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Thyroid Hormones and Resting Heart Rate in Patients Referred to Coronary Angiography

Abstract: Resting heart rate (RHR) is associated with increased risk of cardiovascular morbidity and mortality. Thyroid hormones exert several effects on the cardiovascular system, but the relation between thyroid function and RHR remains to be further established. We evaluated whether measures of thyroid hormone status are associated with RHR in patients referred to coronary angiography. Thyroid-stimulating hormone (TSH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, currently, treatment recommendations are only possible for MMI, but not for alternative ATDs such as propylthiouracil. As thyroid hormones are significantly associated with heart rate (35), it is also tempting to speculate that integrating heart rate data obtained by common wearables such as smartwatches into our DigiThy application may also further improve our model, not only for guiding MMI dosing recommendations but also for detecting (re-) emerging hyperthyroidism. We also have to acknowledge that our work can only be considered a pilot study providing preliminary data on the characteristics and performance of our model and web application.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, currently, treatment recommendations are only possible for MMI, but not for alternative ATDs such as propylthiouracil. As thyroid hormones are significantly associated with heart rate (35), it is also tempting to speculate that integrating heart rate data obtained by common wearables such as smartwatches into our DigiThy application may also further improve our model, not only for guiding MMI dosing recommendations but also for detecting (re-) emerging hyperthyroidism. We also have to acknowledge that our work can only be considered a pilot study providing preliminary data on the characteristics and performance of our model and web application.…”
Section: Discussionmentioning
confidence: 99%
“…However, we conducted sensitivity analysis through multiple imputation and confirmed the robustness of the results. Due to lack of data, the positive association between thyroid hormones and resting heart rate under euthyroid condition, which has been revealed by Steinberger et al [5], was not explored further in this study.…”
Section: The Strengths and Limitations Of The Studymentioning
confidence: 94%
“…Nevertheless, relatively less studies have focused on population with euthyroid status. For example, Steinberger et al have reported free triio dothyronine (FT3) and free thyroxine (FT4) were positively associated with resting heart rate [5]. In addition, several observational studies demonstrated FT3 level was inversely associated with the presence of CAD or the severity of coronary atherosclerosis in euthyroid subjects [6][7][8], however, FT4, FT3 to FT4 ratio (FT3/FT4 ratio) and thyroid stimulating hormone (TSH) were not investigated in those studies.…”
Section: Introductionmentioning
confidence: 99%